Peran Hakim Pengawas Dan Pengamat Dalam Melakukan Pengawasan Atas Putusan Yang Telah Berkekuatan Hukum Tetap Bagi Pelaku Tindak Pidana (Studi di Lembaga Pemasyarakatan Kelas II A Binjai) - Maria Rosalina (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
283 of the Criminal Procedure Code. Superintendent and observer Judges were wise in conducting supervision and observations aimed at obtaining certainty whether the contents of the court's decision had been implemented properly, for example whether prisoners had served their sentences in the jail, did not enter and leave  the jail freely, got room facilities according to their rights, were not released late and so on. However, in its application, there are still many contents of decisions that are not implemented as determined and follow the rules that apply to the prisoners in the jail. Besides, not all of the society at large and prisoners in particular know the existence and duties of the superintendent and observer Judges. Keywords: Superintendent and Observer Judges, Permanent Legal Verdicts, Criminal Offenders.